Perancangan Robot Pembersih Vacuum Pintar Berbasis Mikrocontroller Menggunakan Android - Silalahi, Leonardo; Gustiana, Zelvi; ., Zulham (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 3 (2024): JELIKU Volume 12 No 3, February 2024, 2024)
Robotics innovation has experienced rapid advancements, bringing significant changes to robots, enabling them to adapt to innovative environments. Integrated control systems with microcontrollers and Android platforms facilitate human tasks. Robots are also beneficial in flexible situations such as clinics, homes, workplaces, and hazardous areas. One practical application is the floor-cleaning device with Android control system. In its implementation, the program utilizes the Arduino Uno IDE integrated with a microcontroller. This floor-cleaning device effectively removes dust and dirt. The research on "Design of Intelligent Vacuum Robot Based on Microcontroller Using Android" successfully created a cleaning tool that efficiently assists people in floor cleaning. The microcontroller and Android-based vacuum cleaner are highly useful for cleaning dusty and dirty floors. Therefore, the design of a smart vacuum cleaning robot based on microcontroller and Android becomes a beneficial solution for the community